Trade-off between resistance and persistence in high cell density cultures - F. Beulig; J. Bafna-Rührer; P. E. Jensen; S. H. Kim; A. Patel; V. Kandasamy; C. Steffen; K. Decker; D. Zielinski; L. Yang; E. Özdemir; S. Sudarsan; et al. (mSystems)
ABSTRACT Bacterial growth to high cell densities is commonly observed in infections, microbiomes, and biomanufacturing, yet there is limited understanding of how transcriptional regulation changes to balance between growth and survival under associated stresses. Here, we utilized well-controlled culturing systems to grow wild-type and metabolically engineered Escherichia coli strains into high cell densities (50–80 gcell dry weight L−1) and determine the associated transcriptional dynamics. Knowledge-enriched, machine-learning-based data analytics reveal distinct stress-related gene expression patterns that are consistent with a fundamental trade-off between resistance and persistence. We suggest that this trade-off explains observed growth arrests in high-density cultures and that it results from the disruption of cellular homeostasis, due to re-allocation of limited cellular resources from resistance functions toward increased maintenance requirements. This study deepens our understanding of high-density physiology, illustrates a common link between biomanufacturing and infection, and suggests that persistence phenotypes are programmed as hidden transcriptional states in E. coli.IMPORTANCEThis study presents the first systems-level characterization of Escherichia coli high-cell-density physiology, using an integrated experimental and computational approach. Knowledge-enriched, machine-learning-based analysis of the >470 transcriptomic samples reveals distinct stress-related gene expression patterns that allow the first functional and quantitative description of associated stimulons. The identified stimulons reveal a hitherto undiscovered trade-off between resistance- and persistence-like functions. Our findings have fundamental implications for genome editing of strains optimized for resilience toward stresses of cell-dense environments, particularly those encountered in biomanufacturing.